The spleen tyrosine kinase (SYK): A crucial therapeutic target for diverse liver diseases - Yaping Zhao; Rongrong Liu; Miaomiao Li; Pengfei Liu (Heliyon, 2022)
Spleen tyrosine kinase (SYK) is an enigmatic protein tyrosine kinase, and involved in signal transduction related with lots of cellular processes. It’s highly expressed in the cells of hematopoietic origin and acts as an important therapeutic target in the treatment of autoimmune diseases and allergic disorders. In recent years, more and more evidences indicate that SYK is expressed in non-hematopoietic cells and effectively regulates various non-immune biological responses as well. In this review, we mainly summary the role of SYK in different liver diseases. Robust SYK expression has been discovered in hepatocytes, hepatic stellate cells, as well as Kupffer cells, which participates in the regulation of numerous signal transduction in various liver diseases (e.g. hepatitis, liver fibrosis and hepatocellular carcinoma). In addition, the blockage of SYK activity using small molecule modulators is considered as a significant therapeutic strategy against liver diseases, and both hepatic SYK and non-hepatic SYK could become highly promising therapeutic targets. Totally, even though some critical points about the significance of SYK in liver diseases treatment still need further elaboration, more reliable biotechnical or pharmacological therapy modes will be established based on the better understanding of the relationship between SYK and liver diseases.